An ounce of prevention or a pound of cure? Multi-level modelling on the antecedents of mobile-wallet adoption and the moderating role of e-WoM during COVID-19 - Ahmad M. A. Zamil; Saqib Ali; Petra Poulova; Minhas Akbar; Minhas Akbar (Frontiers in Psychology, 2022)
During the COVID-19 epidemic, personal safety has received increasing attention, leading to behavioral changes. Mobile-wallet (m-wallet) makes it easier for people to keep social distance, which helps stop the spread of the COVID-19 virus. Evolving Internet technology has brought about changes in consumer lifestyle. The current situation of COVID-19 has created a business environment to shift from traditional ways and adopt e-commerce solutions worldwide. Grounded in technology acceptance model (TAM) theory, this study’s objective is two-fold: First, this study intends to examine perceived susceptibility to COVID-19, perceived severity of COVID-19, insecurity and discomfort as the predictors of perceived usefulness (PU) and perceived ease of use (PEOU). Second, the current research intends to test the moderating effect of electronic words-of-mouth (eWOM) on the relationship between attitude and usage intention. Using survey methods, 226 usable responses were collected through a mall intercept survey in Pakistan. Data were analyzed using partial least square (PLS). The results revealed that PEOU and PU positively influence attitude toward M-wallet. This study has found that attitude positively influences the usage intention in adopting M-wallet. The results also support the moderating role of eWOM. These findings contribute to the marketing literature in several ways, particularly in Pakistan. This is the first study to use eWOM as a moderating variable in the TAM theory. In addition, this study adds to the current body of knowledge by considering eWOM as a multi-dimensional construct novel in m-wallet literature.